Blood vessel remodeling in late stage of vascular network reconstruction is essential for peripheral nerve regeneration - Gang Wang; Panjian Lu; Pingping Qiao; Ping Zhang; Xiaodong Cai; Leili Tang; Tianmei Qian; Hongkui Wang (Wiley, 2022)
Abstract One of the bottlenecks of advanced study on tissue engineering in regenerative medicine is rapid and functional vascularization. For a deeper comprehension of vascularization, the exhaustive, dynamic, and three‐dimensional depiction of perfused vascular network reconstruction during peripheral nerve regeneration was performed using Micro‐CT scanning. The 10 mm defect of sciatic nerve in rat was bridged by the autologous or tissue engineered nerve. The blood vessel anastomosis between nerve stumps and autologous nerve accomplished at 4 days to 1 week after surgery, which was a sufficient basis for the mature vascular network re‐establishment. The stronger ability for sprouting angiogenesis and vascular remodeling of autologous nerve compared with tissue engineered nerve was revealed. However, common phases of vascularization in peripheral nerve regeneration were painted: hypoxic initiation, sprouting angiogenesis, and remodeling and maturation. The effect of less‐concerned vascular remodeling on nerve regeneration was further analyzed after nerve crush injury. The blockage of vascular remodeling in late stage by VEGF injection significantly inhibited axons and myelin sheaths regeneration, which attenuated the impulse conduction toward reinnervated muscles. It was illustrated that a large amount of immature blood vessels rather than necessary vascular remodeling elevated local inflammation level in nerve regeneration microenvironment. The figures inspired us to understand the close connections between vascularization and peripheral nerve regeneration from a broader dimension to achieve better constructions, regulations and repair effects of tissue engineered nerves in clinic.